Study of Indonesian Railway Service’s Consumer Behaviour in Accessing Information and Communication Technology of the 4.0 Era - Mudjanarko, Sri Wiwoho; Rasidi, Nawir (ExcelingTech, 2020)
In the era of 4.0, the development of infrastructure of railroad transportation system is facilitated by the use of Information and Communication Technology. This is in line with the increasing needs of users of railway transportation. Train is one of the modes of transportation for Indonesians. Frequency of land transportation users is experiencing an upward trend as service improves as well. Number of users of train services in the period of January-July 2018 reached 242.93 million passengers. It leads to another problem as the ease of users in accessing railroad facilities have not been fulfilled. One of the accesses in need is the availability of Information and Communication Technology. This study aims to determine the behavior of train users in accessing available Information and Communication Technology. The methodology is based on behavioral survey of train users. The survey was conducted with 59 respondents at train station. The result of the study shows that train users really need easy information technology services access as part of significant service in supporting transportation activities.